ENGELSİZ DOĞA ENGELSİZ BİLİM EĞİTİM PROGRAMININ İŞİTME ENGELLİ ÖĞRENCİLERİN BİLİMSEL YARATICILIK DÜZEYLERİNE ETKİSİ. - AKGÜL, Hanife; TAŞ, Esra (Route Educational & Social Science Journal (Ress Journal), 2025)
The purpose of this study is to examine the effect of an educational program designed to increase the creativity and learning skills of hearing-impaired children on the scientific creativity of hearing-impaired students. This study was conducted using a quasi-experimental design method, one of the quantitative research designs. The study group of the research consists of 40 hearing impaired students, 20 in the experimental group and 20 in the control group, who volunteered to participate in the project within the scope of the diagnosed project criteria and who are studying in the 5th, 6th and 7th grades in formal education institutions in the central districts of Kayseri province. The independent variable of the study is the education program, and the dependent variable is the scientific creativity levels of hearing-impaired students. Within the scope of the project ID number 658976, titled "Barrier-Free Nature, Barrier-Free Science", which is supported by the TÜBİTAK 4008 Inclusive Society Practices Support Program for Individuals with Special Needs and carried on behalf of the Kocasinan District National Education Directorate, a science-focused education program that supports creativity for hearing-impaired children was prepared and implemented. Data were collected using the scientific creativity scale. The resulting data set was analyzed using the Mann Whitney U test and the Wilcoxon Signed Rank Test. According to the findings, it was determined that there was a significant increase in the scientific creativity scores of hearing-impaired students who participated in the Barrier-Free Nature, Barrier-Free Science Education Program compared to those who did not participate in this education, and this increase was permanent.